Chimeric Antigen Receptors: The Future of Cancer Immunotherapy - Eqbal, Adam; Li, Ben (The Meducator, 2014)
Chemotherapy, radiation therapy, and surgery are currently the most widely used cancer treatment modalities. Although these therapies have successfully been used to treat various cancers, they are accompanied by significant limitations. Cancer immunotherapy, an emerging field of study named the breakthrough of the year in 2013 is offering hope for an era of new anticancer modalities.1 In addition to serving as a safeguard against infectious disease, the immune system also prevents and delays tumour development.. Scientists have developed various immunotherapeutic treatments, each targeting different aspects of the immune system. One therapy involves genetically engineering T lymphocytes with chimeric antigen receptors (CARs) that enhance the ability of T-cells to recognize and eliminate cancer cells. CART- cell therapy has been highly effective in several clinical trials, eliminating detectable tumour mass in several patients with B-cell malignancies and solid tumours.2 This article will provide background into the field of cancer immunotherapy, the structure and function of CARs, and recent developments in CAR-T-cell therapy.